Prognostic factors for recurrent idiopathic clubfoot deformity: a systematic literature review and meta-analysis - van Schelven, Heleen; Moerman, Sophie; van der Steen, Marieke; Besselaar, Arnold T; Greve, Christian (Acta Orthopaedica, 2022)
Background and purpose — After initial clubfoot correction through Ponseti treatment, recurrence rates range from 26% to 48%. Even though various factors have been associated with increased recurrence risk, systematic assessments of the prognostic capacity of recurrence risk factors and their clinical relevance are lacking. Therefore we assessed clinically relevant prognostic factors for recurrent idiopathic clubfoot deformity after initial correction through Ponseti treatment. Methods — PubMed, Embase, Cinahl, and Web of Science were systematically searched for studies investigating the association between clinically relevant factors and recurrence rates. Prognostic factors were qualitatively assessed and included in the meta-analysis if ≥ 2 studies investigated the same factor and methods were comparable. Results — 34 articles were included in the qualitative synthesis, of which 22 were also included in the meta-analysis. Meta-analysis revealed that poor evertor muscle activity (OR = 255, 95% CI 30–2,190), brace non-compliance (OR = 10, CI 5–21), no additional stretching (OR = 31, CI 10–101), more casts (OR = 3.5, CI 1.6–7.8), lower education level of parents (OR = 1.8, CI 1.2–2.6), non-marital status of parents (OR = 1.8, CI 1.1–3.0), and higher Dimeglio scores (OR = 1.9, CI 1.2–3.3) were associated with higher recurrence rates. Interpretation — Brace non-compliance and poor evertor muscle activity have been identified as main recurrence risk factors and are therefore important to be closely monitored during clinical follow-up of clubfoot patients. Adding additional stretching during the bracing protocol might be promising in the quest to prevent relapse, but scientific evidence for clear clinical treatment recommendations is still limited.